Academic freedom and institutional autonomy in higher education in South Africa: Whereto after decades of discourse and rhetoric? - Saidi, A. (South African Journal of Higher Education, 2025)
Academic freedom (AF) and institutional autonomy (IA) are critical factors for higher education institutions (HEIs) to be able to carry out their core functions effectively, and make the desired societal impact. However, they are also highly contested notions that, since time immemorial, have been the subjects of critical discourses worldwide. This article presents a synthesis of the key issues that stand out from decades of discourse and rhetoric on AF and IA in South Africa. It also illuminates on the roles played by the Council on Higher Education (CHE) in facilitating the discourse, and in providing platforms for deepening the discourse. Furthermore, it poses the question about where to go with issues pertaining to AF and IA after decades of discourse and rhetoric. In exploring the answer to this question, the article posits that the more reasonable route to take after decades of discourse and rhetoric is that of conducting research to acquire empirical insights into the issues raised, and subsequently work towards finding ways and means of addressing them in order to advance, entrench and safeguard AF and IA for the benefit of the sector and all its constituencies. The CHE has decided to take the latter route and, therefore, it has conceptualised and developed a research programme for this purpose. Two research projects that are part of the programme are already underway, with more to follow in the years to come.